SOCIAL-EMOTIONAL PROFILING IN THE PROCESS OF DEVELOPMENTALLY APPROPRIATE PRACTICE IN PREPARATION FOR LEARNING DESIGN - Endang Herawan (Cirebon International Conference on Education and Economics Proceeding, 2024)
The results of observations of students' social-emotional development, especially regarding students' social-emotional development, are still low, because students do not know how to express the emotions they experience in the social environment. It is important for teachers to know students' emotions before learning, which helps teachers to instill meaningful learning in students. The approach in this research uses a qualitative approach with a literature study research method. This research is aimed at the Developmentally Appropriate Practice process in conducting socio-emotional profiling to design learning plans. The result of this research is that lesson planning according to DAP strategy based on socio-emotional profiling should target learning as an interactive process. 45132Teachers need to create an environment where learners can learn actively through exploration and interaction with teachers, friends and the surrounding community. In planning this learning, learning preparation through the observation of students' socio-emotional profiling in the dap process needs to be arranged based on age suitability, individual suitability (talents, interests, strengths and weaknesses and experience in interacting), and social crocodile suitability where the DAP process or method can be carried out in accordance with the developmental stage of students who can show the uniqueness of students in each learning activity.